2008
DOI: 10.1631/jzus.b0710599
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes involved in folate metabolism as maternal risk factors for Down syndrome in China

Abstract: Abstract:Objective: To explore the relationship between genetic polymorphisms in methylenetetrahydrofolate reductase (MTHFR), methionine synthase reductase (MTRR), the central enzymes in folate metabolism that affects DNA methylation and synthesis, and the risk of Down syndrome in China. Methods: Genomic DNA was isolated from the peripheral lymphocytes of 64 mothers of children with Down syndrome and 70 age matched control subjects. Polymerase chain reaction and restriction fragment length polymorphism were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 33 publications
5
46
1
1
Order By: Relevance
“…Several studies have been conducted on the role of folate gene polymorphisms and metabolism in the pathogenesis of DS to provide evidence and new clues (da Silva et al, 2005;Scala et al, 2006;Wang et al, 2008;Biselli et al, 2008b;Coppedè et al, 2006Coppedè et al, , 2009Neagos et al, 2010;Brandalize et al, 2010). The genes investigated as maternal risk factors for DS include methionine synthase, reduced folate carrier 1 and cystathionine-beta-synthase besides MTHFR and MTRR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been conducted on the role of folate gene polymorphisms and metabolism in the pathogenesis of DS to provide evidence and new clues (da Silva et al, 2005;Scala et al, 2006;Wang et al, 2008;Biselli et al, 2008b;Coppedè et al, 2006Coppedè et al, , 2009Neagos et al, 2010;Brandalize et al, 2010). The genes investigated as maternal risk factors for DS include methionine synthase, reduced folate carrier 1 and cystathionine-beta-synthase besides MTHFR and MTRR.…”
Section: Discussionmentioning
confidence: 99%
“…These results provided further evidence for a major role of gene-gene interactions in the assessment of genetic susceptibility to DS. In the last twenty years, few studies have found the MTHFR C677T polymorphism as an independent risk factor for bearing DS children (James et al, 1999;Hobbs et al, 2000;da Silva et al, 2005;Wang et al, 2007bWang et al, , 2008, and most studies conducted in this field have shown a positive view about the cooperation of MTHFR C677T or A1298C polymorphism with other factors including gene polymorphisms and vitamin intake involved in folate and methyl metabolism (O'Leary et al, 2002;da Silva et al, 2005;Acácio et al, 2005;Rai et al, 2006;Biselli et al, 2008b;Meguid et al, 2008;Coppedè et al, 2006Coppedè et al, , 2009Brandalize et al, 2009Brandalize et al, , 2010, where some of them have been in Chinese populations (Wang et al, 2007b(Wang et al, , 2008Liao et al, 2010). It seems that the MTHFR gene mutation acts as a key factor in the assessment of risk to DS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the study by James et al (1999), polymorphisms in the MTHFR gene are the most frequently investigated in attempt to clarify the role of folate and methyl metabolism in the maternal risk for DS (Martínez-Frías et al, 2008). Several studies have associated the MTHFR 677CT polymorphism and the risk of bearing a child with DS (da Silva et al, 2005;Meguid et al, 2008;Sadiq et al, 2011;Wang et al, 2008) as well as with increasing plasma Hcy concentration (P.M. Biselli et al, 2007;da Silva et al, 2005;Narayanan et al, 2004;Ulvik et al, 2007). Another common polymorphism in the MTHFR gene, the substitution of alanine for cytosine at the 1298 position, was already associated with DS risk and increased plasma Hcy concentration (Martínez-Frías et al, 2006;Meguid et al, 2008;Narayanan et al, 2004, Rai et al, 2006Scala et al, 2006;Weisberg et al, 2001).…”
Section: Folate Metabolism Genomic Stability and Maternal Risk For mentioning
confidence: 99%
“…In addition to the MTHFR gene, other genetic polymorphisms involved in the folate pathway seem to modulate the maternal risk for bearing a child with DS (Bosco et al, 2003;J.M. Biselli et al, 2008a;Meguid et al, 2008;Pozzi et al, 2009;Sadiq et al, 2011;Scala et al, 2006;Wang et al, 2008) as well as the concentrations of metabolites involved in the folate pathway (Ananth et al 2007;Barbosa et al, 2008;Cheng et al, 2010;Devos et al, 2008). The MTR 2756 A→G polymorphism has been associated with increased maternal risk for DS in the presence of AG or GG genotypes, as well as when combined with polymorphisms MTRR 66 A→G (MTR 2756AG/MTRR 66AG) (Bosco et al, 2003) and MTHFR 677 C→T (MTHFR 677TT/MTR 2756AA).…”
Section: Folate Metabolism Genomic Stability and Maternal Risk For mentioning
confidence: 99%